An Error Analysis of Indonesian Language Usage in Students’ Initial Academic Writing - Rahmi Magfira (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2025)
This research identifies Indonesian language usage errors within student research proposal manuscripts at Universitas Alkhairaat Palu. The study is driven by the observation that students' academic writing skills often lack linguistic precision, affecting the clarity and scientific quality of their work. Employing a descriptive qualitative method, data was collected via observation, documentation, reading, note-taking, and literature studies. Analysis utilized Krippendorff’s content analysis involving sampling, recording, and context units, validated through source and theory triangulation. The results uncovered 416 errors across six categories. Spelling errors were most frequent with 158 instances, followed by 85 punctuation errors and 72 affixation errors. Additionally, there were 65 capitalization errors, 35 cases of improper italics, and one non-standard reduplication. These findings highlight the critical need for improved linguistic competence in the university's academic environment.